A public strategy under construction? coordination and performance in territorial innovation systems - Fixari, Daniel; Pallez, Frederique (2016)
For several years now, France has been witnessing the development of territorialised public innovation and economic development policies (cluster policies in particular), conducted by various actors, whether the state or the various local authorities. This has triggered the emergence of complex stakeholder systems in the territories, raising doubts about their coordination and performance. It also begs the question of the convergence of public strategies in these conditions. This conjecture, which ties in specifically with the issues of multi-level governance, is based on an empirical study conducted in three French regions, which set out to characterise the workings of these territorial innovation systems and to propose avenues of improvement. Based on this case, we characterise the sources of the apparent complexity of the system and show that, contrary to the voices that call for a reduction in the number of structures, over and above the harmonisation of operations, the establishment of new coordination mechanisms has the additional effect of creating spaces and procedures that allow the gradual formulation of a collective strategy for public actors in the territory. - Reproduced.
Keywords: Administrative structure; Public administration